Tradisi Tale Dalam Kehidupan Masyarakat Kerinci - Ayuthia Mayang Sari (Institut Seni Indonesia Surakarta, 2019)
ABSTRAK This research focuses on the subject matter of Tradition of tale (Traditional Song) in the life of Kerinci People. It aims to see and formulate the existence of Tale. In understanding it, qualitative research methods are used so that the data obtained is descriptive of the behavior of those observed. This study uses a phenomenological point of view that is seeing phenomena as appear appropriate in the field. From the result of the study, it was found that tale is a song of the Kerinci folk in the form of a rhyme. Tale is present in various traditional arts in Kerinci. The tale tradition can be classified according to how to sing it; they are tale that is sung without equipping by music instrument, tale in dancing and tale that is sung equipped by using music instrument. Keywords: Tradition, Tale, Kerinci. ABSTRACT This research focuses on the subject matter of how the tale tradition in the lifes of people in Kerinci. It aims to learn and formulate the existence of tale. The qualitative research method is used to examine the problem in order to present descriptive data relating to the behavior of the people observed. This study uses a phenomenological point of view, namely seeing the phenomena as they appear in the field. The result of the study shows that the tale represents Kerinci folk song in the form of a rhyme. The tale is present in various traditional arts in Kerinci. The tale can be classified based on how it is sung, namely the tale that is sung without musical instruments, tale in the dance and tale that are using musical instruments. Keywords: Tradition, Tale, Kerinci